2009
DOI: 10.1158/1055-9965.epi-09-0298
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Herbal Preparations to Alleviate Climacteric Disorders and Risk of Postmenopausal Breast Cancer in a German Case-Control Study

Abstract: Background:The use of herbal preparations (HEP) to alleviate climacteric disorders is expected to increase as women seek alternatives to menopausal hormone therapy to avoid the associated breast cancer risk. Data are sparse on the long-term effects of HEP containing phytoestrogens and black cohosh on breast cancer risk. Methods: Within a German case-control study, associations between patterns of HEP use and incident breast cancer were investigated in 10,121 postmenopausal women (3,464 cases, 6,657 controls). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
5
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 40 publications
2
35
5
3
Order By: Relevance
“…Black cohosh has not been shown to increase BC risk in postmenopausal women. In contrast, there was a trend for BC risk reduction in healthy women 49 , and a reduced BC recurrence risk in breast BC survivors 50 . Furthermore, black cohosh does not increase mammographic breast density or breast cell proliferation in postmenopausal women 51 .…”
Section: Fractionmentioning
confidence: 89%
“…Black cohosh has not been shown to increase BC risk in postmenopausal women. In contrast, there was a trend for BC risk reduction in healthy women 49 , and a reduced BC recurrence risk in breast BC survivors 50 . Furthermore, black cohosh does not increase mammographic breast density or breast cell proliferation in postmenopausal women 51 .…”
Section: Fractionmentioning
confidence: 89%
“…Of 4 studies examining the impact on breast cancer risk, 2 studies found no significant association, 21,23 and 2 reported an inverse relationship such that black cohosh use was associated with significantly reduced risk of primary breast cancer incidence or breast cancer recurrence, including the study of black cohosh combined with tamoxifen. 24,25 With respect to hot flashes, current Where the comparator is an active agent such as HRT, the effect on the selected endpoints is reported as change over time within the black cohosh group only;: for instance, the effect of 2 months of black cohosh treatment on endometrial thickness, compared to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…A recent very important epidemiologic finding claims that soy protection against cancer is independent from the estrogen receptor (ER) status ( Figure 3), and irrespective of whether a breast cancer is ER-positive (ERq) or ER-negative (ER-) or whether patients are Oriental (14)(15)(16) or Caucasian women (17). This finding clarifies earlier epidemiologic studies, which were not specifically designed to investigate this question.…”
Section: Introductionmentioning
confidence: 51%
“…This finding clarifies earlier epidemiologic studies, which were not specifically designed to investigate this question. Authors of these new epidemiological findings seek a new explanation concerning soy cancer protection mechanisms beyond hormone receptors (16,17).…”
Section: Introductionmentioning
confidence: 99%